MR Imaging Appearance of Long Bone Sarcoidosis - Saha, Debajyoti; Joshi, Ganesh; P. McAnena, Aidan; Tai, Ryan (The ASEAN Journal of Radiology, 2025)
Sarcoidosis is a non-caseating granulomatous disease with common involvement of the lungs and lymph nodes. Osseous involvement is rare, with long bone involvement even rarer. Some of the characteristic MRI findings that point towards osseous sarcoidosis are presence of intra- or perilesional fat. Lesions that involve the long bones usually show no cortical destruction or periosteal reaction, in contrast to small bones, which show cortical destruction or extraosseous extension. In patients with diagnosed sarcoidosis, bone biopsy could be averted in patients having with characteristic findings on MRI. In patients without a diagnosis of sarcoidosis with multiple osseous lesions and aforementioned imaging findings, sarcoidosis can be provided on the differential diagnosis.